The Role of Patience in Coping Mental Problems: A Quranic Perspective - Shinta Nuriya Idatul Alfain; Achmad Khudori Soleh; Muhammad Rafi Yamani (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
Mental health issues have become a growing concern in today's fast-paced and challenging world. In the quest for effective coping strategies, researchers and professionals are increasingly turning to ancient wisdom and religious scriptures for insights. This article explores the role of patience, as emphasized in the Quran, in addressing mental problems and promoting emotional well-being. The study delves into the Quranic verses and teachings that emphasize patience as a virtue and its potential impact on mental health. Drawing from the rich Islamic tradition, the article examines the concept of